Ocupação de conchas pelo ermitão Dardanus insignis na costa norte do estado de São Paulo, Brasil - Frameschi, I. F. [UNESP] (2015)
The pattern of shell occupation by the hermit crab Dardanus insignis (Saussure, 1858) from the subtropical region of southeastern coast of Brazil was investigated in the present study. The percentage of shell types that were occupied and the morphometric relationships between hermit crabs and occupied shells were analyzed from monthly collections conducted during two years (from January 1998 to December 1999). Individuals were categorized according to sex and gonadal maturation, weighed and measured with respect to their cephalothoracic shield length (CSL) and wet weight (CWW). Shells were measured regarding their aperture width (SAW), dry weight (SDW) and internal volume (SIV). A total of 1086 hermit crabs was collected, occupying shells of 11 gastropod species. Olivancillaria urceus (Roding, 1798) was most commonly used by the hermit crab D. insignis, followed by Buccinanops cochlidium (Dillwyn, 1817), and Stramonita haemastoma (Linnaeus, 1767). The highest determination coefficients (r2 > 0.50, p < 0.01) were recorded particularly in the morphometric relationships between CSL vs. CWW and SAW vs. SIV, which are important indication that in this D. insignis population the great majority the animals occupied adequate shells during the two years analysed. The high number of used shell species and relative plasticity in pattern of shell utilization by smaller individuals of D. insignis indicated that occupation is influenced by the shell availability, while larger individuals demonstrated more specialized occupation in Tonna galea (Linnaeus, 1758) shell.